2005
DOI: 10.1128/jvi.79.15.9799-9809.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Divergence, and Evolution of Cell-Free Human Immunodeficiency Virus Type 1 in Vaginal Secretions and Blood of Chronically Infected Women: Associations with Immune Status

Abstract: Most human immunodeficiency virus type 1 (HIV-1) infections are believed to be the result of exposure to the virus in genital secretions. However, prevention and therapeutic strategies are usually based on characterizations of HIV-1 in blood. To understand better the dynamics between HIV-1 quasispecies in the genital tract and blood, we performed heteroduplex assays on amplified env products from cell-free viral RNA in paired vaginal secretion (VS) and blood plasma (BP) samples of 14 women followed for 1.5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
(52 reference statements)
1
32
0
1
Order By: Relevance
“…In the four selected women, the viral genetic diversity between the blood and the genital tract appeared to be significantly different, which was highly suggestive of a compartmentalized genetic evolution of the variant populations between the female genital tract and the systemic compartments at the time of the chronic phase of HIV-1 infection (Table 2). Taken together, these findings supported the hypothesis that the female genital tract is an independent viral anatomic compartment that could harbor genetic variant populations that are distinctly different from those found in the peripheral blood of women recently infected or at the chronic phase of HIV-1 infection (3,4,6,12,15).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the four selected women, the viral genetic diversity between the blood and the genital tract appeared to be significantly different, which was highly suggestive of a compartmentalized genetic evolution of the variant populations between the female genital tract and the systemic compartments at the time of the chronic phase of HIV-1 infection (Table 2). Taken together, these findings supported the hypothesis that the female genital tract is an independent viral anatomic compartment that could harbor genetic variant populations that are distinctly different from those found in the peripheral blood of women recently infected or at the chronic phase of HIV-1 infection (3,4,6,12,15).…”
Section: Discussionsupporting
confidence: 70%
“…Several genetic studies have predicted viral tropism in the female genital tract (4,6) and have suggested that women infected by subtype B virus may harbor distinct CCR5-tropic or CXCR4-tropic viral populations between blood and the genital tract, whereas those infected with other HIV subtypes do not (4,6). In a recent report, in which coreceptor usage was determined using a cell-cell fusion assay, R5-tropic variants were found in both systemic and genital compartments of five clade B HIV-1-infected women at the early stage of the disease (15). The usage of coreceptor CCR5 or CXCR4 by infectious variants present in the female genital tract are likely important determinants implicated in the mechanisms of heterosexual transmission from female to male (3).…”
mentioning
confidence: 99%
“…HIV type 1 (HIV-1) populations isolated from the genital tract in both men and women have been reported as compartmentalized (12,29,43,45,47,48,65,73) when compared to the viruses isolated from the blood or lymphoid tissue. Since the most common route of HIV transmission worldwide is genital exposure (52), the study of HIV populations replicating in the genital tract will help us develop strategies to prevent transmission.…”
mentioning
confidence: 99%
“…Se tivéssemos utilizado o mesmo valor, em lugar de 50 cópias/mL, teriam sido identificados mais três casos. Também se sabe que a diversidade e evolução das cepas do HIV livre vaginal diferem daquelas encontradas no plasma, o que se associa aos níveis de linfócitos CD4 16 . O comportamento diferenciado do HIV no sangue e no meio cérvico-vaginal são aspectos da compartimentalização não estudados nesta casuística.…”
Section: Discussionunclassified